Flow cytometry as a rapid analytical tool to determine physiological responses to changing O2 and iron concentration by Magnetospirillum gryphiswaldense strain MSR-1. Issue 1 (December 2017) - Fernández-Castané, Alfred; Li, Hong; Thomas, Owen; Overton, Tim
Abstract Magnetotactic bacteria (MTB) are a diverse group of bacteria that synthesise magnetosomes, magnetic membrane-bound nanoparticles that have a variety of diagnostic, clinical and biotechnological applications. We present the development of rapid methods using flow cytometry to characterize several aspects of the physiology of the commonly-used MTBMagnetospirillum gryphiswaldense MSR-1. Flow cytometry is an optical technique that rapidly measures characteristics of individual bacteria within a culture, thereby allowing determination of population heterogeneity and also permitting direct analysis of bacteria. Scatter measurements were used to measure and compare bacterial size, shape and morphology. Membrane permeability and polarization were measured using the dyes propidium iodide and bis-(1, 3-dibutylbarbituric acid) trimethine oxonol to determine the viability and 'health' of bacteria. Dyes were also used to determine changes in concentration of intracellular free iron and polyhydroxylakanoate (PHA), a bacterial energy storage polymer. These tools were then used to characterize the responses of MTB to different O2 concentrations and iron-sufficient or iron-limited growth. Rapid analysis of MTB physiology will allow development of bioprocesses for the production of magnetosomes, and will increase understanding of this fascinating and useful group of bacteria.